Developing a Diet of Caterpillars and Mealworms for Mass Rearing of the Predatory Bug Cantheconidea Furcellata (Wolff.)(Hemiptera: Pentatomidae - Sri Ulina, Evawaty (2000)
The asopin bug, Cantheconidea furcellata Wolff., is a promising biological control agent against leaf-eating caterpillars of oil palms. Therefore, the bugs should be mass reared efficiently, effectively and economically. A major challenge to the rearing of the predatory bugs is to overcome the difficulty of keeping them fed with live prey. One approach to improve mass rearing is to reduce the dependence on live caterpillars as a food source. A food item that is readily available and accepted by C. furcellata is the meal worms (larvae of Tenebrio molitor). In a series of experiments, mealworms were compared with the larvae of Spodoptera litura as food sources. The larvae of 5. litura were evaluated live, frozen, reared on artificial diet and natural diets. The results showed that larvae of 5. litura reared on either fresh foliage or artificial diets were the best food sources and that mealworms should be used as a supplementary source. The second part of the study determined the stage of the nymph during which it is critical to provide live larvae of S. litura. The results suggest that developmental and survival rates of second instar nymphs fed live larvae of S. litura was comparable to the control (bugs fed live larvae throughout the nymphal stage). However, in terms of the weight of adult females, the control was the best. The third and final part of the study evaluated the effect of nymphal diet on the reproductive performance of the female bugs. In terms of fecundity and hatchability, feeding the second instar of C. furcellata with live larvae of 5.